Status taxonômico de Ololygon rizibilis (Bokermann, 1964) (Anura: Hylidae) - Caroliny Helena Moreira Fernandes (2020)
Several taxonomic decisions are usually taken from the recognition of morphological characters, a methodology that has dominated the delimitation of species for years and is still used today as the main tool for identification in anurans, assuming an important role as the basis for several studies. However, many descriptions and reviews fail to describe geographic variations, concentrating the study only on morphological characters and taking as evidence few individuals resulting in species, mainly neotropical ones. Cryptic species are neglected when using only the morphological method, since, for these cases, the morphological divergences are non-existent. To understand the plurality of species, it is advantageous for systematically the use of integrative taxonomy, where more than one methodological line is applied, mainly in the study of groups where the occurrence of morphologically similar species is common, as is the case of anurans, making with more accurately descriptions and synonymizing. The objective was to verify if the populations attributed to Ololygon rizibilis from the continental region and from the islands of Santa Catarina and Arvoredo, correspond to one or more independent evolutionary units from studies of integrative taxonomy. The analysis of the present study was structured in three lines of evidence: morphometry, bioacoustic and molecular. The populations were separated into five sample units throughout the distribution. For morphometry it was considered that the allometry associated with the size can cause changes in the shape so the effect of the size was removed and, successively, a manova followed by canonical analysis of variance were performed. A comparative bioacoustics was also performed, with spectral and temporal parameters and finally an analysis with mitochondrial data with the CO1 fragment from genetic distances. Through this approach, we observed that O. rizibilis for individuals that occur in the island of the grove, the morphometric data didn’t point out a significant difference in relation to the populations of the continent. In contrast, the population of the typical location is highlighted from the others. The mitochondrial molecular analysis united all the units in a monophyletic clade, however it was evident that Itati / RS in a separate clade with a molecular distance of 19% in relation to the other , being a possible candidate species. The acoustics showed some subtle differences between the typical location and the other locations on the continent, which, along with morphometry, also suggests a distinct lineage. We conclude from the results that the populations of O. rizibilis consist of three distinct taxonomic units: O. rizibilis referring to the type locality, O. rizibilis with distribution from the south of São Paulo to Santa Catarina, including grove islands and Santa Catarina and population referring to Itati / RS. However, further studies, such as a bioacoustic review of the species, should be addressed in the future